Sistemas Geradores de Subportadoras Ópticas em Loops Paralelos Amplificados com Modulação de Fase - Fonseca Neto, João Pinto da (2023)
In this work, three new C-band (1530 - 1565) nm optical subcarrier generator systems are presented. These systems are based on parallel amplified optical resonators using phase modulators. The systems were computationally simulated using the OptiSystem tool for a 10 GHz spectral spacing between subcarriers. System I generated 135 subcarriers with flatness of 1.9 dB and OSNR of 20 dB. System II generated 53 subcarriers with flatness less than 1 dB and OSNR of 60 dB. And the last proposed system, System III, was able to generate 143 subcarriers with a flatness of 1.4 dB and OSNR of 60 dB.